Comparison of the Meaning of Arabic Borrowed Words in Indonesian and Malay: A Contrastive Semantic Study - Maulana, Arif (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The Arabic language has had a significant influence on the evolution of languages in the Indonesian archipelago, particularly Malay and Indonesian. This impact is evident not only in phonological and morphological aspects but also in semantic aspects. This study aims to analyze the comparative meanings of loanwords from Arabic in Malay and Indonesian using a contrastive semantic approach. The method applied is a qualitative descriptive approach using semantic analysis techniques on various Arabic loanwords identified in Malay and Indonesian dictionaries. The research results indicate that there are several patterns of semantic transformation, namely, semantic expansion, semantic reduction, complete change, and semantic preservation. Furthermore, Malay and Indonesian exhibit distinct differences, particularly in the fields of Islamic law, sociolinguistics, and phonology. This study demonstrates that although Malay and Indonesian belong to the same language family, the development of the meanings of Arabic loanwords in both languages exhibits distinct characteristics.